2021
DOI: 10.3389/fcell.2021.795251
|View full text |Cite
|
Sign up to set email alerts
|

Cell Lineage Infidelity in PDAC Progression and Therapy Resistance

Abstract: Infidelity to cell fate occurs when differentiated cells lose their original identity and either revert to a more multipotent state or transdifferentiate into a different cell type, either within the same embryonic lineage or in an entirely different one. Whilst in certain circumstances, such as in wound repair, this process is beneficial, it can be hijacked by cancer cells to drive disease initiation and progression. Cell phenotype switching has been shown to also serve as a mechanism of drug resistance in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 202 publications
1
14
0
Order By: Relevance
“…Several studies have reported that, in some types of cancer, including PDAC, the expression of squamous lineage markers, including esophagus tissuespeci c genes, correlated with a poor patient prognosis [8, 41,42]. Recent studies have also suggested that a "basal-like/squamous type," which expresses squamous lineage phenotypes, leads to PDAC progression and a poor prognosis [7]. However, the mechanism by which the acquisition of squamous lineage phenotypes led to a poor patient prognosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that, in some types of cancer, including PDAC, the expression of squamous lineage markers, including esophagus tissuespeci c genes, correlated with a poor patient prognosis [8, 41,42]. Recent studies have also suggested that a "basal-like/squamous type," which expresses squamous lineage phenotypes, leads to PDAC progression and a poor prognosis [7]. However, the mechanism by which the acquisition of squamous lineage phenotypes led to a poor patient prognosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Two consensus molecular subtypes of PDAC have recently been proposed based on transcriptomic data: "classical/progenitor type," with a relatively favorable prognosis; and "basal-like/squamous type," with a poor prognosis [7]. Whereas the "classical/progenitor type" preserves the high expression of pancreatic endodermal cell-fate determinants, the "basal-like/squamous type" loses pancreatic identity and expresses many squamous lineage markers related to the upregulation of the ΔNp63 transcription network [7]. Mutation patterns of well-known PDAC driver genes alone cannot explain the difference between these molecular subtypes of PDAC, and the determining mechanism remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the pancreatic tissue, about 90%, is composed by acini where the pancreas acinar cells synthesize and secrete digestive enzymes that are transported to the duodenum through the interconnected ducts [ 8 ]. From these last structures, acini and ducts, the pre-tumoral lesions termed PanINs (pancreas intraepithelial neoplasms) are developed [ 9 ]. There are several types of pancreatic cancer, such as neuroendocrine tumors, squamous cell carcinoma and adenosquamous carcinoma, though more than 90% of cases correspond to the pancreatic adenocarcinoma (PDAC) [ 9 ].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…From these last structures, acini and ducts, the pre-tumoral lesions termed PanINs (pancreas intraepithelial neoplasms) are developed [ 9 ]. There are several types of pancreatic cancer, such as neuroendocrine tumors, squamous cell carcinoma and adenosquamous carcinoma, though more than 90% of cases correspond to the pancreatic adenocarcinoma (PDAC) [ 9 ]. The initial low-grade PanINs potentially progress with morphological and molecular alterations towards high-grade dysplastic lesions and data support that those tissue lesions can eventually evolve to PDAC [ 10 , 11 , 12 ].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…PDAC is currently classified into several subgroups, ranging from 3 to 5 subtypes depending on the system used [24][25][26]. Two major molecular subtypes of PDAC have been found through transcriptome profiling, namely the classical and basal type [27]. The classical type has a better prognosis, demonstrating a clinical relevance.…”
Section: Epigenetic Changes In Pdacmentioning
confidence: 99%